Overview of Knowledge, Attitudes and Skills of Laypeople Post-Application Based Training - Alamsyah Alamsyah; Tut Handayani; Nurcholis Mahfuz; Asri Tuhuri (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
Out-of-hospital cardiac arrest remains a significant public health challenge, with survival often depending on bystander basic life support (BLS). Effective BLS knowledge and practical skills among laypersons are crucial to improving survival outcomes. However, many community members struggle to translate theoretical knowledge into practical action during real-life emergencies. This study aimed to assess the knowledge and skills of laypersons regarding BLS in Takalar Regency, Indonesia. A descriptive quantitative design was employed, involving 60 randomly selected participants. Data were collected using validated and reliable questionnaires to assess both knowledge and skills. The findings revealed that the majority of respondents (72.6%) had moderate knowledge of BLS, while 24.2% demonstrated good knowledge, and none were categorized as poor. Regarding practical skills, 54.8% of respondents passed the skills assessment, 33.9% fell into the doubtful category, and 11.3% failed. These results suggest that while the theoretical understanding of BLS was relatively adequate, practical skill development remained a challenge for many participants. The study emphasizes the need for more effective, continuous, and technology-assisted BLS training programs to improve both knowledge retention and practical skills. Future research should focus on interventional designs to evaluate the long-term effectiveness of these training programs in enhancing BLS performance among laypersons